Observasi Kelengkapan Fasilitas Olahraga sebagai Pendukung Pembelajaran Olahraga di SDN 181 Sukamiskin - Fatihaturohmah, Nurul; Dewangga, Puspa Callista; Tosaini, Salsabila Putri; Mumtazunnisa, Gefira; Yunus, Muhamad; Mulyana, Agus (Indo-MathEdu Intellectuals Journal, 2024)
Education is a learning process for students to develop their potential, as well as in sports. PJOK (Physical Education, Sports and Health) is a lesson that has been given at the elementary school to university levels. This sports education has the goal of forming a healthy lifestyle both physically and mentally. There are several factors that can affect the quality of PJOK learning, including teachers, students, curriculum, teaching methods, and facilities and infrastructure. This research was conducted to find out firsthand the sports facilities owned by SDN 181 Sukamiskin and its impact on the implementation of PJOK. Through descriptive qualitative methods with observations and interviews, it was found that the sports facilities in the school were still inadequate. However, teachers use a variety of creative strategies to overcome these shortcomings, such as modifying sports equipment to keep learning effective and safe. This study emphasizes the importance of facilities and infrastructure to support the success of PJOK learning and provides recommendations for improving sports facilities in the school